Interface management development strategy to improve time performance in the existing oil and gas production modification project on the natuna block - Muhammad Darussalam; Ayomi Dita Rarasati; Mohammad Ichsan (Global Business & Finance Review (GBFR), 2024)
Purpose: Interface management is an effort to overcome interface problems considering that projects in the oil and gas industry are mega projects that involve many parties. This study aims to develop an interface management strategy by identifying interface problems and looking for which interface problems affect time performance on the existing oil and gas field development project in the Natuna Block. Design/methodology/approach: This research is divided into 4 stages, where the first is archive analysis and continued with expert validation, the third is a pilot survey & questionnaire of respondents, and the last is an expert validation. Factor analysis was carried out after expert validation, then validity and reliability tests were carried out with the help of SPSS software. Findings: There are 38 interface problems with nine categories namely, participants, methods/processes, practices, resources, management, information, environment, laws and regulations as well as bids and contracts. Research limitations/implications: This study has limitations in a specific project in specific area with certain product and a context of time/schedule performance. Originality/value: The results of the data analysis will be used to develop a strategy for the development of interface management for the existing oil and gas field modification project in the Natuna Block.
Keywords: 650; Problem factors for interface management; Interface management; Time performance; Existing oil and gas field optimization project; Natuna Block